Bibliometric Analysis of Islamic Finance Within the Halal Sector Industry - Dini Lestari; Wiryono, Sudarso Kaderi (Integrasi Sains Media, 2023)
The possibility of integration between the halal industry and with Islamic financial system can compromise the moving-forward promising business processes that are eligible on the Sharia principle. With the potential for the global, especially the pioneer from predominantly Muslim countries, Islamic finance in the halal industry may be one of the key enablers to support the implementation of growing markets worldwide. This study explores the bibliometric characteristics and trends of Islamic finance and halal business publications indexed in Scopus, Taylor & Francis, ProQuest, Google Scholar, and Crossref. Data were extracted from the five databases used in the paper's research, and free, unbiased searches of all publications published between 1997 and the present were conducted. The terms